Conditions of Business and Holiday Hotels Location. Dolnośląskie, Opolskie and Śląskie Voivodships Case Studies - Daniel Puciato; Teresa Słaby; Bolesław Goranczewski; Agnieszka Gawlik (Barometr Regionalny, 2017)
From the economic point of view the choice of a hotel location is the most important decision for an investor, made at the pre-investment stage of a business project. An attractive building location and a service programme appropriately matched to it determine the profitability level and as a result the development prospects of the hotel. An attempt to determine the most important factors of the location of newly built business and holiday hotels is the aim of the paper as well as the use of documentary and statistical methods in the empirical domain. The spatial scope of the survey comprised Dolnośląskie Voivodship, Opolskie Voivodship and Śląskie Voivodship, while the time covered the years 2000–2009. The analysis of the survey results have shown that the most important factors for business hotel locations comprised transportation access, investment incentives of a planning-administration nature, the supply of tourist services, the level of economic development, the degree of economy internationalization as well as availability of investment areas. In addition, in the analyzed group of holiday hotels the tourist (natural) values, access to skilled hotel staff, investment incentives (of a planning-administration nature), an increase in competition in the hotel sector as well as the supply of tourist services turned out to be statistically significant location factors. After the survey, numerous leads appeared, which in the authors’ opinion should become the subject of further consideration of issues related to hotel location selection conditions.